1990
DOI: 10.1017/s0022149x00012062
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion and abundance of Maritrema arenaria in Semibalanus balanoides in north-east Ireland

Abstract: Infection of the barnacle Semibalanus balanoides with the digenean trematode Maritrema arenaria was investigated at 17 sites along the Co. Down coastline. There was a low background level of infection. Abundance of M. arenaria, however, was substantially greater at sites close to fish factories and at a site close to a sewage works. Aggregation of M. arenaria in S. balanoides was least marked at low mean parasite burdens. The parasitic burden was related more closely to barnacle size at a site of heavy infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bed 5, for example, where cockles had high intensities of infection (Table 2), has one of the highest concentrations of S. plana on the estuary, and also has relatively large numbers of oystercatchers selectively feeding on clams and cockles (Boates & Goss-Custard, 1989). The close association of all three hosts required in the life cycle may best explain such high intensity infections, as has been suggested for other marine host-parasite systems (Carrol et al, 1990;Copeland et al, 1987;Curtis & Hurd, 1983;Irwin & Irwin, 1980). An alternative (but not necessarily independent) explanation is that infection characteristics of trematode larvae on the estuary result from the strength and direction of tidal currents.…”
Section: Discussionmentioning
confidence: 61%
“…Bed 5, for example, where cockles had high intensities of infection (Table 2), has one of the highest concentrations of S. plana on the estuary, and also has relatively large numbers of oystercatchers selectively feeding on clams and cockles (Boates & Goss-Custard, 1989). The close association of all three hosts required in the life cycle may best explain such high intensity infections, as has been suggested for other marine host-parasite systems (Carrol et al, 1990;Copeland et al, 1987;Curtis & Hurd, 1983;Irwin & Irwin, 1980). An alternative (but not necessarily independent) explanation is that infection characteristics of trematode larvae on the estuary result from the strength and direction of tidal currents.…”
Section: Discussionmentioning
confidence: 61%
“…Parasitism may influence zonation in two basic ways: (1) directly through the impact on host abundance or behaviour, and (2) indirectly through parasitic mediation of the interspecific interactions in which host species are engaged. However, empirical evidence for either is still scarce: The trematode Maritrema arenaria may be partly responsible for sudden shoreward declines in the abundance of the encrusting barnacle Semibalanus balanoides (Carrol et al 1990). Trematode infections have also been shown to affect the zonation of periwinkles Littorina spp.…”
Section: Introductionmentioning
confidence: 99%
“…Mitchell & Dessi (1984) found higher incidences of infection in the larger specimens of Balanus (Semibalanus) balanoides. Similarly, Carrol et al (1990) found positive correlation between the size and the number of parasites in the heavily infected specimens.…”
mentioning
confidence: 70%